STAT3, but not Ki-67, expression is independently associated with tumor progression in colorectal carcinoma: A comparative immunohistochemical biomarker analysis - I Gede Putu Adhi Wedharga; Vincentius Michael Willianto; Imelda Theodora; Irene Parengkuan; Bernadette Dian Novita (Universitas Nahdlatul Ulama Surabaya, 2025)
The insidious progression of colorectal carcinoma (CRC) at early stages often hampers timely screening and diagnosis, resulting in delayed intervention and poor clinical outcomes. Ki-67 and Signal Transducer and Activator of Transcription 3 (STAT3) have been widely studied for their roles in tumor proliferation and survival. However, comparative studies assessing their clinicopathological relevance in CRC progression remain limited, and their relative contributions to tumor aggressiveness are unclear. This study aimed to evaluate the clinicopathological significance and association of Ki-67 and STAT3 expression with tumor aggressiveness, focusing on their roles in tumor infiltration and size as indicators of CRC progression. Thirty-eight formalin-fixed, paraffin-embedded (FFPE) CRC tissue specimens were collected from patients undergoing surgical resection for this cross-sectional study. Ki-67 and STAT3 expression were assessed using immunohistochemical (IHC) staining. Clinicopathological data were retrieved from medical records. Protein expression was quantified using inverted mean gray values via digital image analysis. Ki-67 and STAT3 expression levels significantly correlated with tumor infiltration (Ki-67: r = 0.322, p = 0.049; STAT3: r = 0.429, p = 0.007) and size (Ki-67: r = 0.425, p = 0.008; STAT3: r = 0.452, p = 0.004). No significant correlation was found between Ki-67 and STAT3 (r = 0.225, p = 0.175). Only STAT3 was independently associated with infiltration (OR per 1-standard deviation: 4.11, p = 0.043) and size (OR per 1-SD: 3.41, p = 0.047). While both markers are associated with CRC progression, only STAT3 shows an independent association with tumor aggressiveness, underscoring its role beyond cell proliferation and suggesting broader involvement in tumor invasion and progression pathways.